Field dependent–independent cognitive style and creativity from the process and product-oriented approaches: a systematic review - Giancola, Marco; Palmiero, Massimiliano; D’Amico, Simonetta (Creativity Studies, 2022)
Creativity is a multifaceted construct that can be defined both in terms of process (e.g.,divergent thinking) and product (e.g., a poem). Across years, it has been related to different cognitive and personality variables, including cognitive styles. The current systematic review aimed to summarize the literature on the relationships between field dependence–independence and creativity, considering both the creative process and creative production approaches. We selected eight studies using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses rules. Findings revealed that a consistent number of studies focused on creative process mainly in terms of divergent thinking instead of convergent thinking, also providing misleading results. Additionally, only two studies focused on creative production, showing that field independents were more creative than field dependents. Given the contradictory results and the paucity of studies, we concluded that the association between field dependence–independence and creativity needs to be further investigated by more accurate empirical explorations. Limitations and future research directions are discussed.